2016
DOI: 10.11648/j.ijll.20160403.17
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the COERR Writing Project on Cambodian Students’ Attitudes and Writing Performance

Abstract: This study aims to assess the impacts of the Catholic Office for Emergency, Relief and Refugees (COERR)Writing Project (COERRWP) on students' attitudes and their writing performance in correlation with age, gender and language proficiency. In the first stage, a study was conducted to assess 45 students' actual writing performance based on score analysis of their writing test through 2011 to 2014. In the second stage, a quantitative survey questionnaire was administered to a further 80 students from the initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…As a result, Keuk (2009) argues that over 90% of foreigners communicating with Cambodians in English may experience significant misunderstandings due to intelligibility of pronunciation, word choices, grammar and cultural differences. Further, Chan and Srun (2016) point out that there has been a lack of accuracy and proficiency in writing among Cambodian EFL learners. D'Amico ( 2009) and the United Nations Development Program (UNDP) (2011) emphasize that the English skills attained by Cambodian graduates are limited.…”
mentioning
confidence: 99%
“…As a result, Keuk (2009) argues that over 90% of foreigners communicating with Cambodians in English may experience significant misunderstandings due to intelligibility of pronunciation, word choices, grammar and cultural differences. Further, Chan and Srun (2016) point out that there has been a lack of accuracy and proficiency in writing among Cambodian EFL learners. D'Amico ( 2009) and the United Nations Development Program (UNDP) (2011) emphasize that the English skills attained by Cambodian graduates are limited.…”
mentioning
confidence: 99%
“…Overall, no studies have been done on the focus of improving ELF writing accuracy through an AR project. Thus, this study was carried out to fill this void, and in response to a call from Chan and Sotith (2016) that Cambodian EFL students often achieve a poor performance in writing, both in grammatical structures and language use, despite having received formal writing instructions over many years. They suggested that this problem needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, in the past years, there have been empirical studies conducted on English proficiency in terms of its macro skills to contribute to English learning and teaching in Cambodia. Be that as it may, most studies dealt with writing, listening, and speaking (Chan & Srun, 2016;Hong, 2009;Leaph, 2020;Roth & Suppasetseree, 2016;Yin & Chinokul, 2018). There has been, however, little empirical research done in the area of EFL reading literacy in the Cambodian context, despite its importance in English language development.…”
Section: Statement Of the Problemmentioning
confidence: 99%